Opportunities of Reorganising the Urban Environment Using the Example of Quarter Adjacent to Respublican Stadium in Yerevan - Ghazaryan, Astghik; Asteyan, Lilit; Baghumyan, Arno (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
This paper examines the problems of the urban planning environment of the area surrounded by Vardanants, Charents and Shahinyan streets. The aim of the paper is to investigate the current situation, highlight problems and discuss proposed solutions based on these problems. The article is developed by discussing a comprehensive study based on scientific publications, archival documents, projects and studies of the territory, using methods of comparison, generalization and modelling. The results of 3 alternative proposals, which become holistic logical solutions to the problems identified in the study, allow to present directions and discuss the possibilities of further development of the given urban environment. The results of the article can contribute to the development of urban and architectural programs.